Romania after 25 years of transition: historical and meta -structural factors of influence - FLORIN BONCIU (Global Economic Observer, 2016)
The paper analyzes the impact of certain historical and meta-structural factors (such as the adoption of Western style democracy, the adoption of profit as the implicit rule of the game and the accession to the European Union as well as some global factors of influence) on the direction and manifestations of the transition process in Romania after 1989. The aim of the paper is to identify and differentiate the role of historical and objective meta-structure factors versus the role of subjective factors in the establishment of a new institutional and legislative framework in Romania since 1990. The conclusion is that such historical and objective factors are fundamental in understanding what happened in the past 25 years and also for conceiving any feasible strategy for improving the current conditions and characteristics